New Inscriptions from Kalecik/Ankara - Türkan Banu Güler (Gephyra)
In this study, two new inscriptions preserved in the garden of Kalecik Municipality in Kalecik District of Ankara Province are introduced. One of the inscriptions was identified by the Anatolian Civilizations Museum during research conducted in Kalecik in 2019 and was placed in the open-air display area in front of Kalecik Municipality. It is the epitaph of Aurelius Helios, dated to 228 AD. This inscription identifies the previously unknown village of Ōnoukōme and the region named ALEBONŌN (Alebona?) in Kalecik. The second one is thought to be a supplication to God. The inscription contains meaningless letter combinations used to capture the listener's attention in the invocation to the father of the light repository part of Pistis Sophia, a Gnostic text dated to the 3rd-4th centuries AD. Additionally, it includes expressions composed of these combinations found in the magical texts believed to belong to Mithras, preserved in the National Library of France, in a broad codex referred to as the Greek Magical Papyri, also dated to the 3rd century AD.